Proximate composition, sensory evaluation, and mineral content of noodles incorporated with green seaweed, Caulerpa lentillifera, powder - Nur Syakilla; Patricia Matanjun; Ramlah George @ Mohd. Rosli (Springer, 2024)
Caulerpa lentillifera has gained popularity among consumers and researchers in recent years due to its good nutritional profile. The objective of this study is to explore whether the incorporation of different levels of C. lentillifera powder (CLP) concentration in noodles could potentially improve the noodle nutrient profile. The sensory attributes and the nutrient content of the developed noodles were evaluated. Five formulations of noodles containing different percentages of CLP, 0% (F1), 2.5% (F2), 5.0% (F3), 7.5% (F4), and 9.0% (F5) were developed. A sensory evaluation based on a 9-point hedonic scale involving 50 untrained panellists was conducted to determine the best formulation of noodles incorporated with CLP. All formulations were subjected to proximate analyses. From the sensory evaluation, the noodle with the best formulation was F2 (2.5% CLP) as it has the highest score in all sensory attributes tested among all formulations with CLP. Nutrient comparisons between F1 (0% CLP, F2 (2.5% CLP) and a commercial noodle in Malaysia were also made based on its mandatory nutritional facts and mineral profile. The incorporation of 2.5% CLP increased the mineral and protein content of the noodles significantly at p<0.05. In conclusion, CLP incorporation in noodles improves their nutrient profile, and the sensory attributes of noodles containing 2.5% CLP were found to be acceptable.